Evaluating the effect of ormeloxifene on multiple fibroadenomas and mastalgia - Swagata Brahmachari; Vaishali Bhagat; Pooja Patil; Vikram Vasuniya (Wolters Kluwer Medknow Publications, 2021)
Introduction: Most common benign breast conditions presenting in the breast clinics include fibroadenomas and mastalgia, both these conditions cause considerable anxiety in the patients. Among other treatment modalities, the hormonal drug treatments are gaining popularity. Ormeloxifene (centchroman) is an antiestrogenic drug which is shown to have effect in reducing the pain in mastalgia patients and the size of fibroadenoma. Objectives: Ormeloxifene is selective antiestrogen and a nonsteroidal drug. It has a discerning antiestrogen action and hence is useful for the treatment of mastalgia and multiple small fibroadenomas. Hence, the objective of our study was to assess the effect of Ormeloxifene (centchroman) on multiple fibroadenoma and mastalgia. Materials and Methods: Patients with benign breast disease attending our surgery outpatient department from June 2016 to July 2017. Patients were started on Ormeloxifene 30 mg on alternate days for a period of 3 months. Patients were followed up to 6 months after the inception of the study. Parameters recorded include the Visual Analog Scale (VAS) for pain and ultrasonography for breast lump size. Results: Thirty patients were included in the study. We found very good response in the mastalgia; the VAS scores in these patients dropped from 10 to 3 in 90% in the 1st week of introduction of the drug, and at the end of 1 month, almost all of the patients were painless. Overall final response was noted in terms of complete dissolution and change in the size was noted in 34% partial response in 46 %, no changes in 17 % and increase in size of fibroadenoma was noted in only one case. Conclusion: Novex is proved to be safe drug for the treatment of mastalgia and fibroadenoma. Its results were great in mastalgia group. At the end of 6 months, the number of surgeries (if needed) decrease and there is considerable improvement in the patient satisfaction rate.